Innovations in rural and agricultural finance: Biometric technology in rural credit markets: the case of Malawi - Gine, Xavier (International Food Policy Research Institute, 2010)
Identity theft is a common crime the world over. In developing countries, the damage caused by identity theft and identity fraud goes far beyond the individual victim, however, and ultimately creates a direct impediment to progress, particularly in credit markets. Recent research reveals that biometric technology can help reduce these problems